Research on carbon dioxide treatment and utilization technology - Chen Ketong (E3S Web of Conferences)
This paper summarizes the various types of carbon dioxide treatment technology, the current situation, and the development trend, and describes the progress and challenges in the application of carbon dioxide treatment technology at the present stage. It is found that the focus of research and development should be on improving carbon capture efficiency and reducing carbon capture costs. CO2 utilization technology is currently in the industrial demonstration stage, and breaking through the bottleneck of high temperature and high pressure environment, and searching for suitable catalysts to improve the carbon utilization efficiency are the key research directions in the next stage of CO2 utilization technology. CO2 treatment technology needs to overcome the challenges of economic profitability, technological innovation, cost reduction and efficiency enhancement, and policy subsidies and incentives. CO2 bioprocessing technology will become a new mode of CO2 treatment promotion in the future. This study is of reference significance for accurately grasping the research direction of CO2 treatment technology, promoting the progress and innovation of CO2 treatment technology, and accelerating the leapfrog development of CO2 treatment technology.